Gaya Hidup Clubbers pada Usia Emerging Adulthood - Yovita Elvira Sugiharto; Menik Tetha Agustina (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
This study aims to provide an overview of the clubbers' lifestyle during emerging adulthood, focusing on aspects including social interaction, clothing style, music preferences, and the impact on physical and mental health of clubbers. The research employs a descriptive qualitative research method. Data were gathered through in-depth interviews, observations at nightclubs, and documentation. The research subjects consisted of 3 respondents, including 2 females and 1 male. Purposive sampling technique was employed to select participants. The findings of this study acknowledge the significance of emotional expression in the clubbers' lifestyle during emerging adulthood. Social interactions at clubs foster self-confidence and identity enhancement. However, the study also reveals potential impacts on physical and mental health such as altered sleep patterns and stress potential. These findings emphasize the importance of balancing positive emotional expression and individual well-being in navigating the clubbers' lifestyle during the transition to young adulthood.